2021
DOI: 10.3390/ijerph18084357
|View full text |Cite
|
Sign up to set email alerts
|

Family Processes, Parenting Practices, and Psychosocial Maturity of Chinese Youths: A Latent Variable Interaction and Mediation Analysis

Abstract: Development of psychosocial maturity has profound implications for youths’ well-being and positive development in the long run. Nevertheless, little research has investigated the way family socialization contributes to youths’ psychosocial maturity. Both the concepts of family socialization and psychosocial maturity are multifaceted and latent, which may lead to biased results if studied by manifest variables. Also, no existing research has discovered how different family socialization components interact late… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 59 publications
0
18
0
Order By: Relevance
“… 69 And some studies, conducted in China, found that both warmth and control are beneficial and more conducive to improving children’s academic performance. 70 , 71 Maybe, the different definition of the parental control could account for the controversy. As suggested by Liu et al 49 the present study referred the control parenting as parents’ neglect and rejection, which has a negative correlation with the academic performance.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“… 69 And some studies, conducted in China, found that both warmth and control are beneficial and more conducive to improving children’s academic performance. 70 , 71 Maybe, the different definition of the parental control could account for the controversy. As suggested by Liu et al 49 the present study referred the control parenting as parents’ neglect and rejection, which has a negative correlation with the academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…27,72 However, this research found parental control had a negative impact on the academic performance, which is inconsistent with some previous studies in Eastern Culture. [69][70][71] Chao found that Chinese American adolescents from strictness without warmth families reported the better academic achievement. 69 And some studies, conducted in China, found that both warmth and control are beneficial and more conducive to improving children's academic performance.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Adolescents spend a considerable amount of their free time with their peers as parental influence decreases (Ridao et al, 2021). Adolescence is not always the same in all cultural contexts, being differences between European and Anglo-Saxon countries compared to Eastern Societies (Yeung, 2021), especially for athletes (Sun et al, 2020). However, parents always remain as an important source of support to their children (Gallarin and Alonso-Arbiol, 2012).…”
Section: Sports In India Theoretical Framework and The Aim Of This Studymentioning
confidence: 99%